Effect Of Cavity Disinfection Protocols On The Bond Strength And Longevity Of Direct Resin Restorations (The Review of Diabetic Studies, 2025)
Background: Residual bacterial contamination within prepared cavities can compromise the adhesive bond and reduce the longevity of resin restorations. Incorporating cavity disinfection into adhesive protocols has been proposed to improve bonding durability and clinical performance. This study aimed to evaluate the effect of different cavity disinfection protocols on the bond strength and longevity of direct resin restorations.Methods: Eighty sound human premolars were prepared with standardized Class V cavities and randomly divided into four groups (n = 20) according to the disinfection agent used: Group I (control, no disinfectant), Group II (2% chlorhexidine gluconate), Group III (2.5% sodium hypochlorite), and Group IV (70% ethanol). Cavities were restored using a universal adhesive and nano-hybrid composite resin. Half of the specimens from each group were tested immediately for microtensile bond strength, while the other half underwent thermocycling for 10,000 cycles to simulate aging. Failure modes were examined under a stereomicroscope, and data were statistically analyzed using one-way ANOVA and Tukey’s post hoc test (p < 0.05).Results: Significant differences were observed among the groups (p < 0.001). The chlorhexidine group exhibited the highest immediate bond strength (30.5 ± 2.7 MPa) and the greatest aged bond strength after thermocycling (27.1 ± 2.3 MPa), with only an 11.1% reduction. The ethanol group showed moderate performance, while the sodium hypochlorite and control groups displayed lower values, with the control showing the highest reduction after aging (30.9%). Mixed failure modes predominated in disinfected groups, especially in the chlorhexidine group (45%), indicating stronger interfacial bonding.Conclusion: Cavity disinfection significantly enhanced the bond strength and durability of resin restorations. The use of 2% chlorhexidine gluconate prior to adhesive application provided the most stable and long-lasting bond, followed by ethanol and sodium hypochlorite. Incorporating chlorhexidine as a routine cavity disinfectant is recommended to improve the longevity and clinical success of direct resin restorations.